2010
DOI: 10.1111/j.1524-475x.2010.00598.x
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of hypertrophic scarring by using topical anti‐fibrogenic/anti‐inflammatory factors in a rabbit ear model

Abstract: This study investigates the scar-reducing efficacy of topical application of stratifin and acetylsalicylic acid (ASA) in a rabbit ear model. A total of five New Zealand white rabbits with four wounds per ear were examined. Either recombinant stratifin (0.002%) or ASA (0.5%) incorporated in carboxymethyl cellulose gel was topically applied on each wound at postwounding Day 5. Scars were harvested at postwounding Day 28 for histological analysis. The wounds treated with stratifin and ASA showed 82 and 73% reduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
71
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 43 publications
(75 citation statements)
references
References 25 publications
(41 reference statements)
4
71
0
Order By: Relevance
“…They also showed that collagenase mRNA expression and activity in the fibroblast conditioned medium is significantly reduced in HSC fibroblasts compared to the normal ones [4]. Recent studies [5], [6], [7] demonstrate that localized application of agents that are targeted to suppress matrix accumulation provide an approach to specifically reduce scarring.…”
Section: Introductionmentioning
confidence: 99%
“…They also showed that collagenase mRNA expression and activity in the fibroblast conditioned medium is significantly reduced in HSC fibroblasts compared to the normal ones [4]. Recent studies [5], [6], [7] demonstrate that localized application of agents that are targeted to suppress matrix accumulation provide an approach to specifically reduce scarring.…”
Section: Introductionmentioning
confidence: 99%
“…These results suggested that overexpressed miR-185 can inhibit HSFBs growth and that the underlying mechanism was mediated, at least partly, through the suppression of TGF-β1 and Col-1 expression. HS occurs as a result of a pathological wound-healing process, characterized by excess collagen deposition and hyperproliferation of fibroblasts (2,6,8). …”
Section: Discussionmentioning
confidence: 99%
“…During the inflammatory phase of healing, chemotactic and inflammatory factors are induced, which are the prerequisites for subsequent processes, including angiogenesis, re-epithelialization, recruitment, the proliferation of fibroblasts and extracellular matrix (ECM) deposition (7,8). Fibroblasts recruitment and proliferation, the production of ECM, and the inhibition of the production of proteases required to maintain the balance between production and degradation, are influenced predominantly by the fibrogenic growth factors, including insulin-like growth factor, platelet-derived growth factor and transforming growth factor-β (TGF-β) (6).…”
Section: Introductionmentioning
confidence: 99%
“…Finally the tissue was dehydrated, cleared and sealed. Collagen deposition was evaluated by the Image Pro Plus 4.5 software and the relative density of collagen in each group was counted by normalizing to the collagen density in the control group [17]. …”
Section: Methodsmentioning
confidence: 99%